Interpretation Problems with Changes in Indices based on Categorizations - Paul Frijters (Tinbergen Institute, 2000)
In this paper it is argued that occupational and organizational codes maximizethe correspondence between activities and easily observable characteristics atthe time of their development. Over time the codes become less relevant, leadingto the false impression that the segregation of individuals is declining.
Keywords: J31; C43; 330; Arbeitsmarktdiskriminierung; Theorie